The common thread of ibn Khaldun’s educational thought with the learning of the Qur’an - Widiyanto; Nurdin Urbayani (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to analyze the relationship between Ibn Khaldun's educational thought and the learning of the Qur'an at the Bin Baz Islamic Centre Islamic Boarding School. This study uses a qualitative case study method with observation, interview, and documentation approaches. The results of the study show the alignment of learning methods and educational goals between the concept of Ibn Khaldun and those applied in the pesantren. The main findings show the relevance of Ibn Khaldun's educational principles in the modern context at the Bin Baz Islamic Centre Islamic Boarding School. This research contributes to the understanding of the application of classical educational thinking in contemporary educational practice.